Immunological and haematobiochemical studies of enrofloxacin with special reference to residue level following oral administration in goats - Monica, B; Patra, P H; Khargaria, S; Manna, S; Chakraborty, A K; MANDAL, T K (The Indian Journal of Animal Sciences, 2011)
Effect of enrofloxacin on haematobiochemical and immunological parameters alongwith the residual level of enrofloxacin and its metabolite ciprofloxacin in black Bengal goat was carried out following daily oral administration at 5 mg kg-1 body weight for 54 days. A significant decrease in haemoglobin percentage, total leucocyte, erythrocyte and lymphocyte count were noticed in experimental group in different days. But respective biochemical prameters in liver, lung and kidney were not altered in experimental group. A significant decrease in IgG level on different days alongwith lymphocytopenia and decreased lymphocyte number in lymphoid organs of experimental animals indicate immunosuppressive effect. Increased serum AST and ALT activity concomitant with fatty changes and necrosis of liver suggest hepatitis. A degeneration of semineferous tubule and depletion of spermatogenic cells were observed in testis of goats of experimental group. Vital organs contain residues of enrofloxacin and ciprofloxacin.